ANXA1Ac₂₋₂₆ peptide reduces ID1 expression in cervical carcinoma cultures - Prates, Janesly [UNESP]; Franco-Salla, Gabriela Bueno [UNESP]; Santos, Anemari Ramos Dinarte dos; Silva, Wilson Araújo da; Cunha, Bianca Rodrigues da; Tajara, Eloiza Helena; Oliani, Sonia Maria [UNESP]; Rodrigues-Lisoni, Flávia Cristina [UNESP] (Elsevier B. V., 2015)
Cervical cancer is the second most frequent cancer in women worldwide and is associated with genetic alterations, infection with human papilloma virus (HPV), angiogenesis and inflammatory processes. The idea that inflammation is involved in tumorigenesis is supported by the frequent appearance of cancer in areas of chronic inflammation. On the other hand, the inflammatory response is controlled by the action of anti-inflammatory mediators, among these mediators, annexin A1 (ANXA1), a 37 kDa protein was detected as a modulator of inflammatory processes and is expressed by tumor cells. The study was carried out on the epithelial cancer cell line (SiHa) treated with the peptide of annexin A1 (ANXA1Ac2-26). We combined subtraction hybridization approach, Ingenuity Systems software and quantitative PCR, in order to evaluate gene expression influenced by ANXA1. We observed that ANXA1Ac2-26 inhibited proliferation in SiHa cells after 72h. In these cells, 55 genes exhibited changes in expression levels in response to peptide treatment. Six genes were selected and the expression results of 5 up-regulated genes (TPT1, LDHA, NCOA3, HIF1A, RAB13) and one down-regulated gene (ID1) were research by real time quantitative PCR. Four more genes (BMP4, BMPR1B, SMAD1 and SMAD4) of the ID1 pathway were investigated and only one (BMPR1B) shows the same down regulation. The data indicate the involvement of ANXA1Ac2-26 in the altered expression of genes involved in tumorigenic processes, which could potentially be applied as a therapeutic indicator of cervical cancer.
Keywords: Cell culture; Cervical cancer; Differential gene expression; Quantitative pcr; Subtractive hybridization